2019
DOI: 10.1002/hep4.1430
|View full text |Cite
|
Sign up to set email alerts
|

Activation of WNT/Beta‐Catenin Signaling and Regulation of the Farnesoid X Receptor/Beta‐Catenin Complex After Murine Bile Duct Ligation

Abstract: We have recently shown that loss of β‐catenin prevents the development of cholestatic liver injury and fibrosis after bile duct ligation (BDL) due to loss of the inhibitory farnesoid X receptor (FXR)/β‐catenin complex, which results in decreased hepatic bile acids (BAs) through activation of FXR. To further understand the role of Wnt/β‐catenin signaling in regulating BA metabolism and cholestasis, we performed BDL on mice in which hepatocyte Wnt signaling is deficient but β‐catenin is intact (low‐density lipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Mutations in the Wnt/β-catenin signaling pathway have been detected in >90% of colon carcinogenesis cases (24). A close association was recently revealed between FXR and Wnt/β-catenin signaling (25)(26)(27). FXR knockdown in a chronic colitis mouse model resulted in greater susceptibility to tumorigenesis and increased tumor progression (28).…”
Section: Discussionmentioning
confidence: 88%
“…Mutations in the Wnt/β-catenin signaling pathway have been detected in >90% of colon carcinogenesis cases (24). A close association was recently revealed between FXR and Wnt/β-catenin signaling (25)(26)(27). FXR knockdown in a chronic colitis mouse model resulted in greater susceptibility to tumorigenesis and increased tumor progression (28).…”
Section: Discussionmentioning
confidence: 88%
“…[ 27 ] Knockdown of β‐catenin prevented BDL‐induced liver fibrosis due to loss of the FXR/β‐catenin complex, which resulted in FXR activation and reduced BA levels. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Studies using hepatocyte‐specific β‐catenin gene KO in mice revealed dual roles of β‐catenin signaling: Deletion of β‐catenin increased liver injury and fibrosis induced by cholestasis in Mdr2 ‐KO mice, whereas it suppressed liver injury and fibrosis due to cholestasis in bile duct–ligated (BDL) mice. [ 10,11 ]…”
Section: Introductionmentioning
confidence: 99%
“…63 Subsequent studies suggested that CYP7A1 is also either a direct or an indirect target of Wnt signaling as CYP7A1 is suppressed basally in both b-catenin KO and LRP5/6 KO. 64,65 Interestingly, b-catenin can also impact bile acid metabolism through its physical interaction with farnesoid X receptor(FXR), a nuclear receptor that regulates expression of bile acid efflux transporters and represses CYP7A1 expression through activation of small heterodimer partner(SHP). Lack of b-catenin eliminates FXR sequestration, leading to increased availability of FXR to decrease bile acid biosynthesis and stimulate its elimination, with the result that b-catenin KO have less liver injury, fibrosis, and atypical ductular proliferation after experimental cholestasis.…”
Section: Role Of Wnt/b-catenin Signaling In Bile Acid Metabolismmentioning
confidence: 99%
“…Lack of b-catenin eliminates FXR sequestration, leading to increased availability of FXR to decrease bile acid biosynthesis and stimulate its elimination, with the result that b-catenin KO have less liver injury, fibrosis, and atypical ductular proliferation after experimental cholestasis. 64,65 Overexpression of oncogenic b-catenin in mice leads to cholestatic liver disease, whereas in humans, hepatocellular carcinoma with b-catenin gene mutations also exhibits intratumoral cholestasis. 66,67 Because both CYP27 and CYP7A1 are expressed in the perivenous zone along with b-catenin, it is possible that excess b-catenin activates these two bile acid synthesis enzymes either directly or indirectly through inhibition of FXR around the central vein.…”
Section: Role Of Wnt/b-catenin Signaling In Bile Acid Metabolismmentioning
confidence: 99%